PENERAPAN FILSAFAT ILMU BIDANG PENDIDIKAN DI SEKOLAH DASAR - Yelfianita; Yenierita; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
An action or activity that we carry out in a planned and earnest manner in achieving a certain goal is an application. It is an act that puts into practice a theory that has been prepared previously. Related to philosophy and science are two related words, substantially and historically, in which science cannot be separated from the role of philosophy. But on the contrary the development of science can strengthen the existence of philosophy. The birth of philosophy in Greece shows the pattern of thought of the Greeks in which mythological views eventually disappeared and rational statements were dominant. Where according to philosophy, the application is where the mindset that often depends on gods turns into a mindset that depends on ratios. Natural events, such as eclipses are no longer considered as activities of sleeping gods, but are natural occurrences caused by the sun, moon and earth being in parallel lines, so that the moon's shadow falls on part of the earth's surface. Keywords: